Textual Features and Risk Preference Effects on Mental Health Education Among Teenager Students in Chongqing, China - Jiang, Mengyao; Zhang, Zuyue; Kang, Li; Liao, Jing; Wang, Shumin; Lv, Yalan; Zhou, Xiaoyu; Hou, Xiaorong (Frontiers in Psychology, 2022)
Background Mental health is a public health problem of great concern. Previous studies show that textual features and individual psychological characteristics can influence the effect of receiving information. Purpose This study explores whether textual features influence the persuasiveness of teenager students’ mental health education while considering the influence of risk preference. Methods From November to December 2021, a cross-sectional study was conducted among 1,869 teenager students in grade 7–12 in Chongqing, China. Wilcoxon signed-rank test, multiple logistic regression, and subgroup analysis were used to analyze the data. Results Among the four textual features mentioned in this study, a significant difference was reported in the persuasive effects of information with and without numerical features (p < 0.001), and such information tended to include digital features. The result for the symbolic features (p < 0.001) was consistent with the numerical features. The persuasive effects of positive and negative emotional information significantly differed (p < 0.001), with the former showing a better performance. No significant differences were observed between the persuasive effects of information with and without emotional conflicts (p > 0.05). Combined with those from the risk preference analysis, results showed that the regulatory effect of risk preference was only reflected in emotional conflicts. Students who prefer having no emotional conflict in the text showed the characteristics of risk avoidance, or lower grades, or rural or school accommodation. Most teenager students are also risk averse, especially females (or = 2.223, 95%CI:1.755–2.815) and juniors (or = 1.533, 95%CI: 1.198–1.963). Conclusion The numbers, symbols, and positive emotions in the text generate an active effect on teenager students receiving mental health education. Students avoiding risk are inclined to read texts without emotional conflicts. The probability of male choosing texts with positive emotional polarity is 33.5% lower than that of female. Female students and those from lower grades also demonstrate a higher inclination to risk avoidance compared with their male and higher grade counterparts. Therefore, educational materials with different text characteristics should be developed for teenager students with varying characteristics.